BEHAVIOR OF CONCRETE BEAMS REINFORCED IN SHEAR WITH CARBON FIBER REINFORCED POLYMER (Journal of Engineering, 2011)
Carbon fiber reinforced polymers (CFRP) were widely used in strengthening reinforced concrete membersin the last few years, these fibers consist mainly of high strength fibers which increase the member capacity in addition to changing the mode of failure of the reinforced concrete beams. Experimental and theoretical investigations were carried to find the behavior of reinforced concrete beams strengthened by CFRP in shear and bending. The experimental work included testing of 12 beams divided into 4 groups; each group contains 3 beams. The following parameters were taken into consideration: - Concrete crushing strength. - CFRP strengthening location (shear strengthening and both shear and flexure strengthening). Reinforced beams were simply supported subjected to two point loads. Each group consists of three beams; the first beam without CFRP, the second one, is strengthened with CFRP in shear and the third is strengthened with CFRP in both flexure and shear. Four groups with different crushing strength of (12, 20, 30 and 39 MPa). The CFRP sheets are attached externally.It was found that in beam with low crushing strength loads transfer to the CFRP at early stages while inthose of high crushing strength, CFRP contribution only starts when full strength of the beam is fulfilled. Afull bond between CFRP sheets and the concrete is assumed in the theoretical analysis. Comparison between the theoretical and the experimental results revealed the validity of the numerical analysis and the developed methods such that there was a difference of 13% in the ultimate strength for the tested and analyzed beams.